2015
DOI: 10.1016/j.biortech.2014.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic conversion of bio-oil over high-silica zeolites

Abstract: Four high silica zeolites, i.e., HSZ-385, 890, 960, and 990 were utilized for the selective catalytic conversion of bio-oil from Fallopia japonica to certain chemicals in a fixed-bed reactor. The Beta-type HSZ-960 zeolite showed the highest selectivity to hydrocarbons, especially to aromatics as well as PAH compounds with the lowest unwanted chemicals while HSZ-890 showed high selectivity to aromatics. NH3-Temperature Programmed Desorption (TPD) analysis indicated that different amounts of acid sites in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…This method mimics the process of fluid catalytic cracking of crude oil by using zeolites. To date, various zeolites have been tried to upgrade bio-oils [15][16][17][18][19]. Lee et al found that HZSM-5 zeolite can selectively convert oxygenates species in the bio-oil to aromatics compounds due to its small pore opening and strong acidity.…”
Section: Introductionmentioning
confidence: 99%
“…This method mimics the process of fluid catalytic cracking of crude oil by using zeolites. To date, various zeolites have been tried to upgrade bio-oils [15][16][17][18][19]. Lee et al found that HZSM-5 zeolite can selectively convert oxygenates species in the bio-oil to aromatics compounds due to its small pore opening and strong acidity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the impregnation method was shown to be a poor catalyst design with respect to aromatization performance. Widayatno et al [159] explored the performance of some Beta-type zeolites for Fallopia japonica upgrading at 500°C, using 2:0.6 weight ratio of catalyst to biomass. The H-SZ-890 catalyst produced the highest yield of aromatics (30%) with the lowest yield of oxygenates (40%).…”
Section: Effect Of Zeolite Topology and Textural Propertiesmentioning
confidence: 99%
“…S6). These aromatic hydrocarbons have much higher energy density and stability than the oxygenated products in non-CFP, and can be directly used as transportation fuels or commercial chemicals (Huber et al, 2006;Widayatno et al, 2015). CFP of biomass with zeolites thus provides an effective way to rapidly convert solid biomass feedstocks into highly valuable liquid products.…”
Section: Effects Of Mw-fa Pretreatment Of Beech Wood On the Product Dmentioning
confidence: 99%
“…While CFP can rapidly convert biomass to aromatics, its carbon efficiency has yet to be improved to make the conversion process more economically competitive (Lazdovica et al, 2016;Li et al, 2013Li et al, , 2015Widayatno et al, 2015). It is well-known that natural lignocellulosic biomass consists of three major components, i.e., cellulose (40-50 wt.%), hemicellulose (25-35 wt.%), and lignin (15-20 wt.%) (Alonso et al, 2010;Huber et al, 2006).…”
Section: Introductionmentioning
confidence: 99%